The THE IMPACT OF MASTERY GOAL ORIENTATION IN MODERATING CREATIVE SELF-EFFICACY ON FEEDBACK RECEIVED FOR IMPROVING INNOVATIVE WORK BEHAVIOR AND CREATIVE PERFORMANCE IN INDONESIAN TEACHERS - Pus, Riski Puspita Angraini; Syah , Tantri Yanuar Rachmat (Fakultas Ilmu Pendidikan Universitas Negeri Surabaya, 2023)
Imagination is an imperative characteristic that instructors must possess to fathom different issues within the world of education with the aim that learning can be achieved optimally. Apart from the inherent ability, imagination can also be influenced by several factors. External factors, specifically the role of feedback, and internal factors, specifically creative self-efficacy, creative work behavior, and leadership goal orientation. This study aims to identify the impact of creative self-efficacy, creative work behavior, and leadership goal orientation on imaginative performance, which is influenced by feedback for all instructors in Indonesia. This study was conducted using a purposive sampling method involving 265 instructors from Professional High Schools (SMK) in Indonesia, covering various subjects and having at least one semester of teaching experience. Data were analyzed using Structural Equation Modeling (SEM) with SmartPLS 3.2.9. Some of the findings in this study indicate that creative self-efficacy and creative work behavior have an influence on imaginative performance. Feedback also plays a moderating role in the relationship between creative self-efficacy and imaginative performance factors.